The Influence of Language Attitude and Linguistic Intelligence on Creative Thinking - Kholid Jarnudi; Sholeh Hidayat; Syafrizal Syafrizal (PT ARRUS Intelektual Indonesia, 2023)
This research aims to analyze and describe the influence of language attitudes and linguistic intelligence on creative thinking. This research was carried out at MAN 1 Serang City, Banten, Indonesia with a sample of 152 class XI students spread across science, social studies, and religion departments. The research instruments used in this research were questionnaires and tests. This research is correlation research using a quantitative approach and the data analysis technique used in this research is regression. Based on the results of the data analysis, it can be concluded that there is an influence of language attitudes and linguistic intelligence on creative thinking. Simultaneous language attitudes and linguistic intelligence in creative thinking are a strong synergy. They serve as tools that can stimulate and facilitate creative thinking in individuals while enabling them to communicate and collaborate in ways that support the development of innovative ideas and creative problem-solving. The two work together to form a more robust and diverse creative mind.